2010
DOI: 10.1016/j.jacc.2010.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Does Elevated C-Reactive Protein Increase Atrial Fibrillation Risk?

Abstract: Elevated plasma CRP robustly associated with increased risk of atrial fibrillation; however, genetically elevated CRP levels did not. This suggests that elevated plasma CRP per se does not increase atrial fibrillation risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(60 citation statements)
references
References 16 publications
5
48
2
3
Order By: Relevance
“…These results are surprising especially when viewed in light of findings from another South African study that showed that Africans have significantly higher levels of CRP when compared to white counterparts [30]. It remains controversial whether CRP is merely a marker [31,32] or indeed causal [33][34][35] in the development of CVD, with strong evidence supporting either statement. Notwithstanding this controversy, CRP remains an important marker to include when investigating CVD development.…”
Section: Discussionmentioning
confidence: 96%
“…These results are surprising especially when viewed in light of findings from another South African study that showed that Africans have significantly higher levels of CRP when compared to white counterparts [30]. It remains controversial whether CRP is merely a marker [31,32] or indeed causal [33][34][35] in the development of CVD, with strong evidence supporting either statement. Notwithstanding this controversy, CRP remains an important marker to include when investigating CVD development.…”
Section: Discussionmentioning
confidence: 96%
“…C - reactive protein has been associated with chronicity in AF (16). Studies have shown that levels of CRP correlate with inflammation, fibrosis, and remodeling (17).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, elevated C-reactive protein (CRP) is known to be a marker of inflammation and increased CRP levels have been described in people with type 2 diabetes (23). Elevated plasma CRP is robustly associated with increased risk of AF (24). So that increased CRP levels may be responsible for diabetes-AF connection.…”
Section: Discussionmentioning
confidence: 99%